2016
DOI: 10.1016/j.indcrop.2015.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Growth of spring canola (Brassica napus) under deficit irrigation in Western Nebraska

Abstract: a b s t r a c tDrought is a periodic occurrence in the High Plains of the U.S.A.; thereby low-water using crops are desired. Canola, a biofuel and food oil, has been studied in the region under rain-fed conditions for several years. The study's objective was to measure plant growth, seed yield, and oil characteristic of canola at four levels of applied water in western Nebraska. The cultivar Hyola 357 Magnum was exposed to rain-fed only (RF), and irrigated with 10 (LI), 20 (MI), and 30 (HI) cm water. Adding ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Water requirement declines sharply after seed set to harvest (Hergert et al, 2016). From a study in Nebraska, Pavlista et al (2016) concluded that >200 mm of water is required for adequate vegetative growth, and that >400 mm of water is necessary for high yield (3 Mg ha −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water requirement declines sharply after seed set to harvest (Hergert et al, 2016). From a study in Nebraska, Pavlista et al (2016) concluded that >200 mm of water is required for adequate vegetative growth, and that >400 mm of water is necessary for high yield (3 Mg ha −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Canola yield (Mg ha −1 ) and water use (mm of water) during the crop growing season. Data for the figure were collected from Nielson (1997), Johnston et al (2002), Hergert et al, (2016), Pavlista et al (2016), and unpublished winter canola irrigation trial data in Finney, Kansas (Kisekka, Ciampitti et al, unpublished data, 2017). Slope of the regression line represents the water use efficiency (Mg ha −1 mm −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The concept of deficit irrigation has been known for many years (English, 1990) and has been researched as a production strategy on many conventional crops in Nebraska (Garrity et al, 1982;Hergert et al, 1993;Klocke, et al, Payero, et al, 2006;1989;Schneekloth et al, 1991) and more recently on canola (Hergert et al, 2016;Pavlista et al, 2016b), but not camelina. The goal of deficit irrigation is to manage irrigation timing so the resulting water stress has less of a negative impact on grain yield.…”
Section: Introductionmentioning
confidence: 99%
“…The water deficit, especially in the flowering period can affect grain development (Avila et al, 2004;Gunasekera et al, 2006;Tesfamariam et al, 2010) preventing early maturing hybrids to express its maximum physiological potential. According to Pavlista et al (2016), water availability needs to be constant, without interruption and throughout the crop cycle, to achieve high yield and obtain high physiological quality seeds. Mean values for the second crop season is verified in Table 8.…”
Section: Electrical Conductivitymentioning
confidence: 99%